The Concept of Akrasia in D. Husak’s Theory of Criminal Responsibility and the Advantages of Its Alternative - Gediminas Šataitis (Problemos)
This article explores two concepts of akrasia and their relation to the ascription of responsibility in Douglas Husak’s theory of criminal responsibility. Ever since Plato’s Protagoras, the problem of akrasia has been tightly related to the issue of moral knowledge. By using influential texts of ancient and Christian ethics, as well as contemporary research on akratic behavior, this article outlines a different conception of akrasia, one that is based on intrapersonal conflict. In his theory, Husak employs the concept of akrasia related to moral knowledge-ignorance, albeit sourcing its presuppositions from contemporary skeptics rather than from ancient philosophy. Yet, Husak’s theory is not skeptical. The article highlights the main drawbacks of this theory. These drawbacks are grounded in Husak’s conception of the akratic agent and the ascription of responsibility to such an agent. Their analysis reveals the advantages of the concept of akrasia based on intrapersonal conflict for constructing a non-skeptical theory of criminal responsibility.